Kundry must die: stage direction and authenticity - Moura, Vítor (2015)
Although I’m intuitively inclined to accept the priority of production, there is much to consider in the arguments of more conservative accounts about stage direction. This is what this paper proposes, a panoramic view of what should count as proper performance of a notational dramatic text. In order to do that, I’ll be juggling with two different kinds of materials. On the one hand, the arguments with which philosophers of music, in particular, have tried to define what should count as “correct” performance. On the other hand, the philosophical discussion about what a theatrical performance is (descriptively as well as normatively). At the intersection of both lines of thought we expect to find some illumination as to whether Kundry should live or die.